AMERICAN FRONTIERSMEN IN 19TH CENTURY AS REPRESENTED IN AUGUSTUS B. LONGSTREET’S “THE FIGHT” - Elisabeth Oseanita Pukan (Universitas Stikubank (UNISBANK) Semarang, 2016)
Particular literary works have a great significance that they can also act as historicaldocuments through which readers can trace back the phenomena of the society in theera in which those literary works were written. One of those literary works isAugustus Baldwin Longstreet’s “The Fight”, a short story which was said to be thecornerstone of the birth of southwestern humor literature. Falling into the category ofliterature of the frontier, this short story depicts the lives of Georgian people asfrontiersmen in the early 19th century. This study’s objective is to unveil howAmerican frontiersmen is represented by the author and how this representation isrelated to the Georgian society at that time. This study found that there was a historyof violence among frontiersmen, there was glorifying masculinity, and there was dirteatingperversion due to the harshness of the nature of the frontier and the socialcondition at that time.Key words: humor, southwestern humor, frontier, frontiersmen